TANGGUNG JAWAB DEVELOPER TERHADAP KONSUMEN DALAM PENYERAHAN UNIT APARTEMEN KEMANG VIEW: The Responsibility of Developers towards Consumers in the Handover of Kemang View Apartments Units - Anastasya Islamiah; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
The residential sector is a priority area for consumer protection in Indonesia under Presidential Regulation No. 50 of 2017 due to frequent consumer complaints. One notable case is the Kemang View Apartment dispute, where the developer failed to fulfill consumer rights and neglected its contractual obligations. This study examines the developer’s responsibility in handing over apartment units based on Law No. 8 of 1999 on Consumer Protection. The analysis shows that the handover of units is regulated by Law No. 8 of 1999 and Law No. 20 of 2011 on Apartments. The developer’s failure to deliver units as agreed constitutes a breach of the Sale and Purchase Agreement and violates consumer rights. At present, the developer has not fulfilled its responsibilities, resulting in unremedied consumer losses.